2005
DOI: 10.1179/joc.2005.17.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Microdilution, Etest and Disk Diffusion Methods for Antifungal Susceptibility Testing of Clinical Strains ofTrichosporonSpp.

Abstract: Trichosporon spp are well recognized as pathogens capable of causing invasive disease. Despite the increasing frequency and severity of trichosporonosis, data on the antifungal susceptibility of Trichosporon spp. are limited and recommendations for in vitro testing of this fungus are not included in the guidelines of the National Committee for Clinical Laboratory Standards. The purpose of this study was to determine the in vitro susceptibility of clinical Trichosporon isolates to systemic antifungals. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…Nevertheless, the in vitro bacterial sensitivity test is still a routine procedure for clinical purposes, based on which proper antibiotics are selected to treat the infection. [24][25][26] …”
Section: Bmentioning
confidence: 98%
“…Nevertheless, the in vitro bacterial sensitivity test is still a routine procedure for clinical purposes, based on which proper antibiotics are selected to treat the infection. [24][25][26] …”
Section: Bmentioning
confidence: 98%
“…While some of these used the CLSI or similar broth microdilution methodology (2, 4, 6, 18, 28-30), others applied Etest or disk diffusion assays (18,31,32). Using the CLSI M27-A2 method, MIC-2 as the endpoint, and 72 h as the incubation period, Thompson et al (29) reported MIC 90 values of 2, 0.06, 0.25, and 0.125 g/ml for fluconazole, voriconazole, posaconazole, and isavuconazole, respectively, for 40 isolates of T. asahii.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo and in vitro activities of triazoles against Trichosporon species are higher than that of AMB (5,14). Trevino (13). In another study by Kalkanci et al, it has been emphasized that the efficacy of FCZ with MIC GM 13.66 was very low and the most active drug was VOR with 0.154 MIC GM (10).…”
Section: Discussionmentioning
confidence: 99%